RATIONAL EMOTIVE BEHAVIOR THERAPY UNTUK MENGURANGI SELF INJURY - Nurul Mar’atis Sholeha; As’ad; Wawan Juandi (Konseling At-Tawazun, 2024)
Self-injury is self-harming behavior that is carried out intentionally because you cannot express your emotions without the intention of committing suicide. The subject in this study was a 20 year old male counselee, with a disorder that often hurts himself. The subject does this because he feels that nothing can calm his mind and understand his emotions. Rational Emotive Behavior Therapy was used in this research because it can identify and change irrational thoughts through cognitive therapy with individual counseling services. This research is action research with two cycles. After the subject realizes that irrational thoughts are the main cause, the subject is directed to good thoughts and a good outlet for emotions. The results of this research are that REBT with cognitive techniques can be a means for subjects to fight their irrational thoughts.